Features of translation Korean realia into Kazakh language (Journal of Oriental Studies, 2017)
This article is devoted to theoretical and practical analysis of translationproblems in Kazakhstan through a review of the major difficulties intranslating the realia from Korean into Kazakh language in a literary text. Asyou know, way of life, climatic factors, geographic location, history and societystrongly influence the formation of some of the features of the cultureand is displayed in the language of the nation. The importance of this worklies in the fact that today the problems of classification, characteristics andthe translation of realia are still open.